HIGH-DOSE EPIRUBICIN IN CHEMOTHERAPY REFRACTORY NONSEMINOMATOUS GERM-CELL CANCER - A PHASE-II STUDY - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1992)
Eighteen patients with progressive disseminated, platinum-resistant germ cell tumors were treated with epirubicin 35 mg/m2, every 3 weeks. One patient had stable disease, 17 developed progression. Myelosuppression was dose-limiting. One patient died of neutropenic septicemia. High-dose epirubicin is not active against platinum-resistant germ cell cancer.
Keywords: EPIRUBICIN; GERM CELL CANCER; TESTICULAR CANCER; TESTICULAR CANCER